2010
DOI: 10.1097/pas.0b013e3181db84aa
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Novel Stem Cell Markers SALL4, OCT4, NANOG, SOX2, UTF1, and TCL1 in Primary Mediastinal Germ Cell Tumors

Abstract: Primary mediastinal germ cell tumors (GCTs) are rare and sometimes they pose diagnostic difficulty without immunohistochemical studies. Here, we investigated the diagnostic utility of 6 stem cell markers (SCMs) SALL4, OCT4, NANOG, SOX2, UTF1, and TCL1 in 16 primary mediastinal seminomas, 3 embryonal carcinomas (ECs), 10 yolk sac tumors (YSTs), 7 teratomas (4 mature, 3 immature), and 1 choriocarcinoma. The percentage of tumor cells stained was scored as: 0 (no tumor cell staining), 1+ (< or =30%), 2+ (31% to 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
94
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 45 publications
7
94
0
1
Order By: Relevance
“…Primary extragonadal germ cell tumors are uncommon tumors that most often occur in the midline structures and mediastinum, but they can also occur in many other organs, not only in children but also in adults. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Morphologically, primary extragonadal germ cell tumors can mimic many types of non-germ cell tumors. For example, mediastinal seminomas may mimic type B thymomas and embryonal carcinoma may mimic other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary extragonadal germ cell tumors are uncommon tumors that most often occur in the midline structures and mediastinum, but they can also occur in many other organs, not only in children but also in adults. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Morphologically, primary extragonadal germ cell tumors can mimic many types of non-germ cell tumors. For example, mediastinal seminomas may mimic type B thymomas and embryonal carcinoma may mimic other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The result of SALL4 in these germ cell tumors was previously reported. [10][11][12] To determine its specificity, we also examined LIN28 in 82 primary non-germ cell tumors of the CNS and in 17 primary mediastinal epithelial tumors (thymomas and thymic carcinomas). The immunohistochemical status of LIN28 in other extragonadal non-germ cell tumors (103 carcinomas, 91 sarcomas, 83 lymphomas, 9 plasmacytomas, 12 mesotheliomas, and 9 melanomas) was previously reported.…”
mentioning
confidence: 99%
“…In adults, SALL4 expression is normally restricted to CD34+ hematopoietic stem/ progenitor cells , and in adult mice, SALL4 is also predominantly expressed in testes and ovaries (Kohlhase et al, 2002b). Nonetheless, SALL4 expression is reported in numerous malignancies, such as precursor B-cell lymphoblastic lymphoma , myelodysplastic syndromes , acute myeloid leukemia (Shuai et al, 2009), endometriotic samples (Forte et al, 2009), ovarian germ cell tumors (Cao et al, 2009a), all types of testicular germ cell tumors (GCTs) (Cao et al, 2009c), all metastatic seminomas/ dysgerminomas and embryonal carcinomas (Cao et al, 2009b), and primary mediastinal yolk sac tumors (Liu et al, 2010). It is suggested that SALL4 may not only be important in the pathogenesis of GCTs, especially to maintain their poorly differentiated status, but can also be used as a highly specific marker to confirm the germ cell origin of a metastatic tumor, due to its sensitivity and specificity (Cao et al, 2009a,b,c).…”
Section: Introductionmentioning
confidence: 99%
“…However, Nanog, Sox2, and Oct4 (also known as Pou5f1) are linked to tumorigenesis as well ( [8][9][10] and reviewed in ref. [11]).…”
Section: Introductionmentioning
confidence: 99%